2022
DOI: 10.7196/samj.2022.v112i3.16024
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory parameters associated with prolonged hospital length of stay in COVID-19 patients in Johannesburg, South Africa

Abstract: COVID-19, caused by SARS-CoV-2, has wreaked havoc on global economies and healthcare systems around the world. The World Health Organization declared COVID-19 a pandemic in March 2020. [1] Waves of new infection and new, more transmissible SARS-CoV-2 variants have led to protracted lockdown regulations in many countries. [2][3][4] While lockdown has been an effective method of 'flattening the curve' , it is not a socially or economically sustainable solution for the long term. The ability of healthcare systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
(80 reference statements)
2
4
0
Order By: Relevance
“…Our findings are consistent with previous studies demonstrating an association between higher NLR scores and an increase in in-hospital mortality 11,13 and critical illness requiring ICU admission or transfer 15 . Our study was consistent with some but not all that higher NLR scores were not associated with LOS 16–19 . The studies supporting NLR association with longer hospital LOS were shown with NLR scores greater than even the high tertile group of our study 16,17 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings are consistent with previous studies demonstrating an association between higher NLR scores and an increase in in-hospital mortality 11,13 and critical illness requiring ICU admission or transfer 15 . Our study was consistent with some but not all that higher NLR scores were not associated with LOS 16–19 . The studies supporting NLR association with longer hospital LOS were shown with NLR scores greater than even the high tertile group of our study 16,17 .…”
Section: Discussionsupporting
confidence: 93%
“…Our study was consistent with some but not all that higher NLR scores were not associated with LOS 16–19 . The studies supporting NLR association with longer hospital LOS were shown with NLR scores greater than even the high tertile group of our study 16,17 . Our study was consistent with a prior study that showed admission NLR did not predict 30-day postdischarge mortality 20 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The relationship between these indices (for example, NLR) and disease severity is not as unequivocal as that of IL-6 and CRP. Increased NLR levels has been observed in patients with Covid-19 in Johannesburg, South Africa but this parameter was not significantly related to prolonged LOS ( 35 ). The NLR has been shown to be useful in identifying young patients with severe Covid-19 (≤40 years) ( 36 ).…”
Section: Discussionmentioning
confidence: 99%